Karakteristik dan Mutu Arang Kayu Jati (Tectona grandis) dengan Sistem Pengarangan Campuran pada Metode Tungku Drum (The Quality and Characteristics of Teak (Tectona grandis) Charcoal Made by Mixed Carbonisation in Drum Kiln) - Salim, Rais (Kementerian Perindustrian, 2016)
Charcoal was the residue of the decomposition of wood from heating process whereas the chemical component was carbon. One of the charcoal production methods used was a kiln drum with carbonisation mixed system. This research aimed to identify and analyse the quality of teak wood charcoal made by carbonisation mixed system with the addition of sawdust teak using kiln drum method. Teak wood pieced in 5-10 cm diameter were charred by the addition of sawdust (70:30) to maintain the temperature process ranged between 4000C and 4500C. The parameters that were observed were yield, water content, volatile substance content, ash content, bonded carbon content, the percentage of charcoal that retained at 6.35 cm sieve and that passed the 3.18 cm sieve, calorific value, density and color. The results were then analyzed descriptively and been compared to the SNI 01-1683-1989. The yield of teak charcoal in this experiment was 21.3%, while water, volatile substance and ash content were 3.93%, 16.57%, and 3.25%, respectively. The percentage of charcoal retained at 6.35 cm sieve was 88,68%, and the ones passed 3.18 cm sieve was 1, 96%. The charcoalâs bonded carbon content was 80.18%, itâs calorific value was 7141 cal / g; and the color was black.Keywords: carbon, sawdust, carbonization temperatures